2014
DOI: 10.1039/c3sm52522h
|View full text |Cite
|
Sign up to set email alerts
|

Membrane curvature based lipid sorting using a nanoparticle patterned substrate

Abstract: Cellular membranes contain a variety of shapes that likely act as motifs for sorting lipids and proteins. To understand the sorting that takes place within cells, a continuous, fluid bilayer with regions of membrane curvature was designed and characterized using confocal fluorescence and total internal reflection fluorescence microscopy techniques. A supported lipid bilayer was formed over fluorescently labelled nanoparticles deposited on a glass surface. The lipid composition and membrane shape are separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 46 publications
6
56
0
Order By: Relevance
“…Although the Pearson’s correlation coefficients are quite small, DHPE is significantly higher than HDA, indicating that the lipids are weakly associated with curvature, but DHPE associates more. It is interesting to note that in our bilayer system, the bilayer composition is symmetric and higher degrees of sorting have been observed when we added lipids specifically to the upper leaflet only [18]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Pearson’s correlation coefficients are quite small, DHPE is significantly higher than HDA, indicating that the lipids are weakly associated with curvature, but DHPE associates more. It is interesting to note that in our bilayer system, the bilayer composition is symmetric and higher degrees of sorting have been observed when we added lipids specifically to the upper leaflet only [18]. …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that molecules avoid curvature. It is also difficult to find trajectories that transition from flat to curved regions, yet FRAP data has shown that lipids’ NP positions recover [18] and the single molecule tracking of SB-DHPE clearly demonstrates that movement of molecules at sites of curvature is very confined (Figure 5). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,62 Furthermore, the NP size can modulate the corona formation due to curvature-related changes in the membrane composition 6368 and NP-protein interactions. 26,69 The National Institutes of Health defines nanomaterials as materials with characteristic length scales < 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…These methods were mostly based on fluorescence and included Förster Resonance Energy Transfer (FRET) 25 , Fluorescence Correlation Spectroscopy (FCS) 26 , Fluorescence Recovery after Photobleaching (FRAP) 27,28 , Fluorescence Anisotropy 29 and Generalized Polarization (GP) of the Laurdan probe 30 . These studies have included investigations of lipid behavior in nanoparticle-modified lipid bilayer systems 28,31,32 . Some of these techniques can – in principle – be implemented on the single-cell or even -virus level.…”
mentioning
confidence: 99%